Sosialisasi Permainan Sudoku pada Pembelajaran Matematika untuk Siswa SMP Negeri 8 Padang - Deby Erdriani; Dewi Devita; Laila Marhayati (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pengabdian Kepada Masyarakat (PKM) is a form of the Tridharma of Higher Education. This PKM is proposed to carry out socialization and educational activities at SMP Negeri 8 Padang. This community service was made with the aim of increasing students' interest and motivation and enthusiasm for mathematics, creating a new atmosphere in learning mathematics and providing information to students that mathematics can also be used as a game to sharpen the brain and abilities. This service uses a math game, sudoku. In practice we will use active and cooperative learning methods, where students will be actively involved by providing opportunities for them to explore, solve problems both individually and in groups.